Pembangunan Irigasi Air Tanah Dangkal Untuk Peningkatan Produktivitas Usaha Tani Desa Sambirejo Kabupaten Langkat - Rizki Efrida; Tondi Amirsyah Putra; Citra Utami (University of Muhammadiyah Sumatera Utara, 2019)
Water is one of the most important elements of the agricultural sector. Water availability should be assured for plants to grow well throughout the year. However, not all areas in Indonesia are fortunate to have technical irrigation so that water availability can be arranged throughout the year. The lack of water availability resulted in crops being unable to produce well, resulting in reduced farmer's income. The things that are behind the team of activities devotion to the community to apply their knowledge to the farmers who still make use of rain-water irrigation such as in the village Sambirejo Langkat District. The main and priority issues of Sambirejo village, especially the Bina Tani Farmers group, are the unavailability of water in the dry season to irrigate the rice fields. Unavailability of water reduces the productivity of farmers who should be able to harvest 3 times to only 2 times a year. It takes an alternative water source as a water provider in the dry season. The solutions offered in this program are the construction of shallow groundwater irrigation. This method utilizes groundwater as a water provider during the dry season. Keywords: Farmer, Dry Season, Irrigation, Groundwater